Peningkatan Kapasitas Pembelajaran Santri Melalui Literasi Digital Dan Pemanfaatan Media Sosial Di Pondok Pesantren - Sodik, Mohamad; Nur Syayidah, Laily; Nur Isma , Luluk (LP3M IAIFA Kediri, 2024)
Nowadays, digital literacy is very important because computerization is increasingly sophisticated, making it easier to find references for the study of science. By using digital literacy, it will be more cost-effective than having to buy books, and in fact, by using digital literacy the information will always be updated. Social media is now very popular among people because it can provide new information. The aim of this service is to teach and assist students to use digital literacy to increase learning capacity, and also to manage social media as a medium to strengthen brotherhood between fellow students. The PKM process carried out at the Al-Hikmah Srengat Blitar Islamic Boarding School consists of three stages: First, problem identification is a study carried out by the PKM team, teachers, school principals, and leaders at the Islamic boarding school to find out how strong their literacy skills are. digital owned by the students. The results of this PKM are teaching and mentoring regarding digital literacy studies and the use of social media such as Facebook, and Instagram by creating groups as a communication medium for students, as well as the practice of installing the Zoom application and its benefits, as well as using the Google Meet application.